A multiperiod drayage problem with customer-dependent service periods - Ghezelsoflu, Ali; Di Francesco, Massimo; Frangioni, Antonio; Zuddas, Paola (Computers & operations research, 2021)
•A new drayage problem with multiple service periods and flexibility in their change.•A path-based model with all feasible routes.•A “Price-and-Branch” algorithm in acyclic network.•A compact arc-flow formulation based on this network.•Analysis of flexibility, costs and potential discount fees. We investigate a multiperiod drayage problem in which customers request transportation services over several days, possibly leaving the carrier some flexibility to change service periods. We compare three approaches for the problem: a path-based model with all feasible routes, a “Price-and-Branch” algorithm in which the pricing is formulated as a collection of shortest path problems in a cunningly constructed acyclic network, and a compact arc-flow formulation based on this network. The experiments shows that the latter formulation is the most efficient, and can solve to optimality instances of real-world size (and beyond) in time compatible with typical operational constraints. Also, the models allow us to assess that limited amounts of flexibility from customers can significantly improve routing costs for the carrier while decreasing customers’ cost as well.